Toward Ending the HIV Epidemic: Temporal Trends and Disparities in Early ART Initiation and Early Viral Suppression Among People Newly Entering HIV Care in the United States, 2012–2018. (22nd July 2022) - Li, Jun; Humes, Elizabeth; Lee, Jennifer S; Althoff, Keri N; Colasanti, Jonathan A; Bosch, Ronald J; Horberg, Michael; Rebeiro, Peter F; Silverberg, Michael J; Nijhawan, Ank E; Parcesepe, Angela; Gill, John; et al.
Abstract: Background: In 2012, the US Department of Health and Human Services updated their HIV treatment guidelines to recommend antiretroviral therapy (ART) for all people with HIV (PWH) regardless of CD4 count. We investigated recent trends and disparities in early receipt of ART prescription and subsequent viral suppression (VS). Methods: We examined data from ART-naïve PWH newly presenting to HIV care at 13 North American AIDS Cohort Collaboration on Research and Design clinical cohorts in the United States during 2012–2018. We calculated the cumulative incidence of early ART (within 30 days of entry into care) and early VS (within 6 months of ART initiation) using the Kaplan-Meier survival function. Discrete time-to-event models were fit to estimate unadjusted and adjusted associations of early ART and VS with sociodemographic and clinical factors. Results: Among 11 853 eligible ART-naïve PWH, the cumulative incidence of early ART increased from 42% in 2012 to 82% in 2018. The cumulative incidence of early VS among the 8613 PWH who initiated ART increased from 83% in 2012 to 93% in 2018. In multivariable models, factors independently associated with delayed ART and VS included non-Hispanic/Latino Black race, residence in the South census region, being a male with injection drug use acquisition risk, and history of substance use disorder (SUD; all P ≤ .05). Conclusions: Early ART initiation and VS have substantially improved in the United States since the release of universal treatment guidelines. Disparities by factors related to social determinants of health and SUD demand focused attention on and services for some subpopulations.